Critical characteristics of corrosion product film obtained by fluid structure interaction. Issue 12 (16th January 2013) - Zhu, X. L.; Lu, X. F.; Ling, X.
Abstract The critical characteristics of corrosion product film (CPF) were investigated, and the mechanism of flow‐accelerated corrosion (FAC) was discussed by improving the multiple reference frame method (MRF) using the space temporary coordinate system. The improved MRF was used to accomplish fluid structure interaction (FSI) numerical simulation for FAC testing machine with a pre‐filming specimen. The new numerical method for the simulation of the critical characteristics of the CPF was proposed by coupling FSI and contact analysis in COMSOL Multiphysics software based on Hertz theory, which was used to calculate the critical characteristics of the specimen. The results reveal that the deformation and stress of the CPF increased with increasing temperature and flow velocity. The critical flow velocity was higher than the pre‐filming flow velocity and increased with increasing temperature. The calculation results are consistent with those of the linear polarization experiment.